Optimization of safflower sowing time in northern Karnataka: Optimization of safflower sowing time in northern Karnataka - G SOMANAGOUDA,; R H PATIL,; M P BASAVARAJAPPA, (Journal of Oilseeds Research, 2020)
Three safflower genotypes (A-1, NARI-6 and NARI-57) were tested across three sowing times (1 to 30 October) at fortnight interval during 2014-15 and 2015-16 with an objective to find out the best sowing time for safflower crop and to identify best performing variety in northern dry zone of Karnataka. It was concluded that early sowing (first fortnight of October) as well as variety A1 were the best to give higher seed yield.